ANALISIS PENGARUH KEPEMIMPINAN, MOTIVASI, LINGKUNGAN KERJA TERHADAP KINERJA PERUSAHAAN “ STUDI KASUS PADA PABRIK GETAS SEHATI DI JL AIR MAWAR PANGKALPINANG - Pratama, Ricky; Ruben Manullang, Rizal; Maharani, Yunita (Jurnal Progresif Manajemen Bisnis, 2022)
The purpose of this research is to prove that Leadership, Motivation, and Work Environment have a simultaneous effect on company performance . This research was conducted on students of the Bangka Belitung Islands Province. The sample in this study were company employees who were still actively working at the Sehati Getas Factory. This study used a quantitative approach by distributing questionnaires to 25 respondents using the propotionate stratified random sampling. Questionnaires were distributed directly to respondents who were in the work environment at the Getas Sehati Factory. The data were statistically processed with the JASP program, namely the t test model, f test, and determinant coefficient test (R2). The results showed that together Leadership, Motivation, and Work Environment had a positive and significant impact on the company’s performance at the Getas Sehati Factory at JL Air Mawar Pangkal Pinang. Partially, the variables of leadership, motivation, and work environment have a significant effect on purchasing decisions. The value R Square is 0.918, which means that the variables that can be explained by Leadership, Motivation, and Work Environment are 91.80%, while the remaining 8.20% can be explained by variables not examined in this study.